Crisis Thermometer for housing market recommendations. (November 2015) - Kaklauskas, A.; Daniunas, A.; Binkyte, A.; Kliukas, R.; Kazokaitis, P.; Kaklauskas, G.; Juozapaitis, A.; Banaitis, A.; Budryte, L.
Highlights: The global innovativeness of the Crisis Thermometer for housing market recommendations, developed by these authors, constitutes. Defining the "temperature" in the housing market. Compiling numerous alternative recommendations applicable to a specific user. Performing an analysis of these tips and selecting out the ten most rational ones. Performing a validation of the model and Crisis Thermometer. Abstract: Early warning, neural networks, expert, decision support, fuzzy and other systems, barometers, housing and real estate bubble indexes have been developed in an effort to analyze and manage crises in housing market. Scholarly literature employs various concepts of housing market crises concepts, including overheated, heating-up, stable, stagnant market, freezing, healthy housing. There are numerous interest groups operating at the meso and macro levels of the housing market who would appreciate receiving recommendations during the various stages of a crisis in the housing market. Therefore, the Crisis Thermometer for housing market recommendations was developed applying the aforementioned intellectual systems and concepts along with the long-term backgrounds of these authors. Different countries frequently select different strategies and tactics in their efforts to lessen the effects from a housing market crisis. This is entirely natural due to differing economies and markets of different countries, as well as their respective legal, institutional, technological, technical, social, cultural, political, psychological, ethical and other kinds of aspects. Traditionally an analysis of a housing market crisis is grounded on economic, legal, institutional and political aspects. Less attention is paid to social, cultural, ethical, psychological, emotional, religious, demographic, spiritual and educational aspects of crisis management. These sorts of factors are additionally used for assessing a housing market crisis with the aid of the Thermometer and for submitting personalized recommendations. The innovativeness of the Crisis Thermometer, developed by the authors herein, is primarily that it automatically determines the "temperature" of housing market, compiles numerous alternative recommendations applicable to a specific user, performs a multiple criteria analysis of these recommendations and selects out the ten most rational ones for that user. This article overviews the housing market crisis management model and its respective Thermometer and presents a practical example to demonstrate how the developed Thermometer works. This article also presents the validation of the proposed model and Crisis Thermometer.